Will give 100 points!!
![Will give 100 points class=](https://us-static.z-dn.net/files/d82/6b384c0e9464328058103b7716e93e43.png)
Answer:
[tex]\large{\boxed{\sf 2x+h-4}}[/tex]
Explanation:
f(x) = x² - 4x + 3
f(x + h) = (x + h)² - 4(x + h) + 3
Solving Steps:
[tex]\rightarrow \sf \dfrac{(x + h)^2 - 4(x + h) + 3 - (x^2 - 4x + 3)}{h}[/tex]
[tex]\rightarrow \sf \dfrac{x^2 + 2xh + h^2 - 4x -4h+3-x^2+4x-3}{h}[/tex]
[tex]\sf \rightarrow \dfrac{2xh+h^2-4h}{h}[/tex]
[tex]\rightarrow \sf 2x+h-4[/tex]
Put values
[tex]\\ \rm\Rrightarrow \dfrac{x^2+2xh+h^2-4x-4h+3-x^2+4x-3}{h}[/tex]
[tex]\\ \rm\Rrightarrow \dfrac{2xh+h^2-4h}{h}[/tex]
[tex]\\ \rm\Rrightarrow \dfrac{h(2x+h-4)}{h}[/tex]
[tex]\\ \rm\Rrightarrow 2x+h-4[/tex]